Transcontinental dialogues: Activist alliances with Indigenous peoples of Canada, Mexico, and Australia - Alcalà-i-Rams , Marc; Romaniello, Alessandro (Quaderns de l’Institut Català d’Antropologia, 2022)
Transcontinental dialogues: Activist alliances with Indigenous peoples of Canada, Mexico, and Australia Rosalva Aída Hernández Castillo, Suzi Hutchings i Brian Noble (eds.) (2019) Tucson: The University of Arizona Press 264 p. ISBN: 978-08-1653-857-7